Five new deep-sea species of nudibranchs (Gastropoda: Heterobranchia: Cladobranchia) from the Northeast Pacific - Valdés, Ángel; Lundsten, Lonny; Wilson, Nerida G. (Zootaxa, 2018)
Increased exploration of northeastern Pacific deep-sea habitats has revealed a diverse and often poorly-known invertebrate community, including a number of undescribed species of nudibranchs studied herein. We used morphology to distinguish several new species from their congeners, and generated data where possible for mitochondrial (COI, 16S) and nuclear markers (H3) to place them in a phylogenetic context. We described here Tritonia nigritigris sp. nov., Dendronotus claguei sp. nov., Ziminella vrijenhoeki sp. nov., Cuthona methana sp. nov., Aeolidia libitinaria sp. nov. and redescribed Zeusia herculea (Bergh, 1894). Another species of Tritonia is described but not named due to the absence of reproductive system information. Although there are difficulties in collection from deep-sea habitats, only two of our new species are known from single specimens. As with many other deep-sea regions, we expect the number of new species from this region to increase with further exploration. Because the deep regions of the northeast Pacific are particularly vulnerable to the effects of decreasing oxygenation due to climate change, we consider that documenting this fauna has some level of urgency.